Non-interrupting user interfaces for electronic body-worn swim devices - Förster, K.; Bächlin, M.; Tröster, G. (Proceedings of the 2nd International Conference on Pervasive Technologies Related to Assistive Environments (PETRA 2009), 2009)
We evaluate three different non-interrupting user interfaces that give feedback to a swimmer while swimming. We designed three interfaces for audio, visual and haptic feedback. These three systems were used in an experiment to give commands to a swimmer. The recognition rate and the reaction time for each modality was determined. The systems do not restrict the users in their swim movements. For the visual and the haptic interfaces the results are promising as 70%-100% of the triggered events were recognized correctly. The reaction time of the subjects was in the range of 1.25 to 2.25 seconds. With the audio feedback we achieved less than 70% of recognized events and a reaction time about twice as long as for the visual or haptic feedback. The audio feedback is therefore not appropriate while swimming.